PENGUJIAN PENGARUH TETUA BETINA TERHADAP SIFAT TOLERANSI PADA NAUNGAN KEDELAI [Glycine max (L.) Merill] - Handayani, Titin (Universitas Sebelas Maret, 2008)
This study was conducted at Green House IPB Cikabbayan Darmaga Research Station. Soybean tolerance genotype (Ceneng) was crossed with sensitive genotype (Godek A) to study the mode of inheritance in tolerance to shade. Reciprocal cross were also made in soybean Ceneng and Godek A to study maternal effect. This experiment was conducted under artificial shading by using paranet with light intensity 75%. Material genetic were used Ceneng, Godek A, F1 and F1’ that were planted according to complete Randomized Experimental Design. The result of “t” test showed that anatomical , morphological characters, and molecular marker for tolerance and sensitive genotype was significant difference, while was no significant in F1 and F1’. This experiment can be concluded that there was no maternal effect found in the soybean crossing between tolerance and sensitive genotype.